Manejo de percevejos e mosca-branca em soja - Rohrig, Alberto (2021)
Stink bugs and whiteflies are major concerns for pest management in Brazilian soybean production, causing severe economic losses to soybean growers and leading to excessive application of insecticides per crop cycle. Despite biological differences, these two sapsucking or feeding pests often occur together in soybeans fields and can be successfully managed with the same insecticide spray, reducing operational costs to the growers. The aim of this work was to evaluate the efficacy of eleven chemical insecticides in the control of stink bugs and whiteflies under field conditions, in two crop seasons. The experimental design was randomized blocks with four replicates. Two insecticide sprays were made with an interval of 14 days apart. The results from ANOVA and Tukey post-hoc test (P≤0.05) revealed significant difference among the treatments for the control of stink bugs and whiteflies. Acetamiprid + bifenthrin (75 + 75 g a.i. ha-1) was the most efficient treatment for the control of stink bugs, reaching 97.8% of insect mortality. Cyantraniliprole + bifenthrin (50 + 50 g a.i. ha-1) was the most efficient treatment for the control of whiteflies, reaching 78.8% of insect mortality. This treatment also presented the highest combined control of stink bugs and whiteflies, reaching 83.5% of insect mortality. This, the insecticide treatment can be recommended for the combined management of stink bugs and whiteflies in soybean.